Pengaruh Social Media Marketing Terhadap Brand Equity dan Dampaknya Pada Minat Beli Produk Merek Pobosoccer (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2022)
This study aims to determine the effect of social media marketing on brand equity and its impact on buying interest in Pobosoccer brand products. The population in this study are active followers of Pobosoccer social media who have purchased Pobosoccer products, the number of which is unknown. The number of samples in this study were 100 responses. Data collection techniques in the study used a questionnaire. The analytical technique in this research is path analysis, which is to analyze the causal relationship between exogenous variables and endogenous variables. The results of the research on the structure of the first model show that the value of the Beta Coefficient of entertainment variables is 0.159, customization is 0.190, interaction is 0.300, trendiness is 0.181, and word of mouth is 0.189, where each of these variables has a significance value of <0.05, which means the entertainment variable, customization, interaction, trendiness, and word of mouth have a positive and significant effect on the brand equity variable. While the results of the research on the structure of the second model show the Beta coefficient of the entertainment variable is 0.158, customization is 0.147, interaction is 0.168, trendiness is 0.138, word of mouth is 0.238, and brand equity is 0.189.